Beyond the Interview Guide: Experiences of Practically and Mindfully Implementing Interview Guidelines When Conducting Research With Children and Adolescents With Chronic Conditions and Their Siblings - Rogers, Laura G.; Shearer, Kathleen; Hryniuk, Sarah Southon; Ray, Lynne; Rempel, Gwen R. (International journal of qualitative methods, 2021)
Children and adolescents who live with chronic conditions are rarely participants in research specifically focused on meeting their needs, nor in intervention planning research. There are, however, special considerations required when conducting research with children and adolescents. This article offers Interview Guidelines designed to ensure children and adolescents’ control of and comfort with interviewing and to maximize the caliber of ethically co-constructed data. We developed, tested, and revised these guidelines with 80 children and adolescents aged 5 to 17 years: 27 with complex Congenital Heart Disease (CCHD) (5–17 years) and 13 with Early Onset Scoliosis (5–12 years) and 28 siblings (7–17 years). The guidelines were further tested with 12 adolescents with Adolescent Idiopathic Scoliosis (10–16 years) and 10 children and adolescents with CCHD (8–12 years). The children and adolescents recounted stories about their everyday life and activities through digitally recorded face-to-face interviews that were transcribed. Detailed field notes were recorded before and after the interview. Our Interview Guidelines address ethics, informed assent and consent, pre-interview planning, establishing trust, and engaging children and adolescents in research. Special attention is given to involving parents in pre-interview planning and disclosing sensitive information post interview. Involving children and adolescents as research participants to gain information from them, not only about them, will assist those in planning appropriate intervention research to meet the needs of children and adolescents living with chronic conditions and their siblings.